ANTIOXIDANT AND HEPATOPROTECTIVE EFFECT OF CHITOSAN VERSUS VITAMIN E IN EXPERIMENTAL CARBON TETRACHLORIDE-INDUCED LIVER INJURIES - LOGIN, Cristian Cezar; NAGY, Andras-Laszlo; MUREŞAN, Adriana; MOLDOVAN, Remus; DECEA, Nicoleta; DAICOVICIU, Doina; CLICHICI, Simona (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The aim of our study was to assess the hepatoprotective and antioxidant effects of chitosan as compared with vitamin E in experimental toxic liver injury induced by carbon tetrachloride. Blood and liver samples were collected in order to assess hepatocytolisis (AST, ALT), oxidative stress (MDA, carbonyl proteins, GSH, SH groups, SOD and CAT), and histopathology examination was performed in order to assess inflammation and fibrosis. Liver enzymes level showed a significant, progressive increase after repeated exposure to CCl4, first in liver tissue, then in the blood. Malondialdehyde and carbonyl proteins significantly increased, and GSH progressively decreased. Chitosan increased the GSH in the liver tissue to a value superior to that of the control group and decreased the AST and MDA level both in the liver and in the blood to values comparable to that of control group. Chitosan decreased carbonyl proteins level in the liver but slightly increased them in the blood. Vitamin E had similar effects concerning liver function and lipid peroxidation, but paradoxically, it induced protein peroxidation both in blood and in liver tissue. Histological modifications support the observed biochemical changes.